2017
DOI: 10.1097/pec.0000000000001312
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Trial of Cardiopulmonary Feedback Devices and Their Impact on Infant Chest Compression Quality

Abstract: Objectives In effort to improve chest compression quality among health care providers, numerous feedback devices have been developed. Few studies, however, have focused on the use of cardiopulmonary resuscitation feedback devices for infants and children. This study evaluated the quality of chest compressions with standard team-leader coaching, a metronome (MetroTimer by ONYX Apps), and visual feedback (SkillGuide Cardiopulmonary Feedback Device) during simulated infant cardiopulmonary resuscitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
1
16
0
3
Order By: Relevance
“…Studies published by Lee et al [30] also indicate 120 CPM as the optimal chest compression rate, while noting that higher compression rates can reduce chest relaxation. Similar conclusions can also be drawn from studies by Smereka et al [8], as well as from studies by other authors [31][32][33].…”
Section: Discussionsupporting
confidence: 87%
“…Studies published by Lee et al [30] also indicate 120 CPM as the optimal chest compression rate, while noting that higher compression rates can reduce chest relaxation. Similar conclusions can also be drawn from studies by Smereka et al [8], as well as from studies by other authors [31][32][33].…”
Section: Discussionsupporting
confidence: 87%
“…Following removal of 196 duplicates, 681 sources were screened via titles and abstracts, resulting in 201 possible relevant studies. Upon full text analysis, 32 studies met inclusion criteria and were included in our review including 14 randomised controlled trials (RCTs) [14,17,18,20,23,24,29,32,33,38,40,42,44,45], 08 randomised trials (RTs) [25][26][27][28]31,36,37,41] and 10 randomised cross-over trials (RCOTs) [15,16,19,21,22,30,34,35,39,46]. The flow chart of the search and selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Metrics such as chest compression rate, chest compression depth, recoil, handoff time, fatigue reduction and general quality of CPR, significantly improved as a result of the use of ARTF during training in those studies. Conversely, few studies have demonstrated mixed effects with some results showing only modest improvements in CPR skill acquisition but not clinically significant to be considered true change [14,33,46] or no improvement at all [21] and others finding improved CPR measures with the use of ARTF but those results being no better or no worse than those associated with feedback from a trained human instructor [42].…”
Section: Analysis Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of feedback devices in conjunction with short duration, on‐site training has been shown in other studies to improve compression depth and rate compliance . A recent study that looked at the quality of simulated infant CPR, however, showed no clinically significant difference in technique or chest compression quality when instructor‐led training was compared with use of a metronome or feedback device …”
Section: Discussionmentioning
confidence: 99%